Antiretroviral Adherence Level Necessary for HIV Viral Suppression Using Real-World Data. (1st November 2019) - Byrd, Kathy K.; Hou, John G.; Hazen, Ron; Kirkham, Heather; Suzuki, Sumihiro; Clay, Patrick G.; Bush, Tim; Camp, Nasima M.; Weidle, Paul J.; Delpino, Ambrose
Abstract : Background: A benchmark of near-perfect adherence (≥95%) to antiretroviral therapy (ART) is often cited as necessary for HIV viral suppression. However, given newer, more effective ART medications, the threshold for viral suppression may be lower. We estimated the minimum ART adherence level necessary to achieve viral suppression. Settings: The Patient-centered HIV Care Model demonstration project. Methods: Adherence to ART was calculated using the proportion of days covered measure for the 365-day period before each viral load test result, and grouped into 5 categories (<50%, 50% to <80%, 80% to <85%, 85% to <90%, and ≥90%). Binomial regression analyses were conducted to determine factors associated with viral suppression (HIV RNA <200 copies/mL); demographics, proportion of days covered category, and ART regimen type were explanatory variables. Generalized estimating equations with an exchangeable working correlation matrix accounted for correlation within subjects. In addition, probit regression models were used to estimate adherence levels required to achieve viral suppression in 90% of HIV viral load tests. Results: The adjusted odds of viral suppression did not differ between persons with an adherence level of 80% to <85% or 85% to <90% and those with an adherence level of ≥90%. In addition, the overall estimated adherence level necessary to achieve viral suppression in 90% of viral load tests was 82% and varied by regimen type; integrase inhibitor- and nonnucleoside reverse transcriptase inhibitor-based regimens achieved 90% viral suppression with adherence levels of 75% and 78%, respectively. Conclusions: The ART adherence level necessary to reach HIV viral suppression may be lower than previously thought and may be regimen-dependent.